2018
DOI: 10.1016/j.biologicals.2018.09.001
|View full text |Cite|
|
Sign up to set email alerts
|

Establishment of the first International Standard for human anti-typhoid capsular Vi polysaccharide IgG

Abstract: Vi capsular polysaccharide (Vi) conjugate vaccines, which can prevent typhoid in infants and young children, are being developed. Comparative immunogenicity studies are facilitated by an International Standard (IS) for human anti-Vi IgG. 16/138, a pool of sera from volunteers which received either Vi conjugate vaccine or plain Vi vaccine, was assessed as an IS alongside U.S. reference reagent Vi-IgGR1, 2011. Samples were tested in a commercial ELISA (n = 7), a standardised ELISA based on biotinylated Vi (n = 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 23 publications
3
23
0
Order By: Relevance
“…A good correlation between our in-house ELISA and Vacczyme ELISA was observed for anti-Vi IgG levels based on either US reference Vi IgG R1, 2011 or the Vacczyme ELISA's calibrator in this study. This result supports the outcome of the previous collaborative study [18], which showed that our in-house ELISA and the Vacczyme determined a similar anti-Vi IgG potency for the US reference. Based on the correlation, we developed a statistical model to transform data from the in-house ELISA (μg/ml) to the Vacczyme ELISA (EU/ml) in the Vi-DT phase 1 study [19].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…A good correlation between our in-house ELISA and Vacczyme ELISA was observed for anti-Vi IgG levels based on either US reference Vi IgG R1, 2011 or the Vacczyme ELISA's calibrator in this study. This result supports the outcome of the previous collaborative study [18], which showed that our in-house ELISA and the Vacczyme determined a similar anti-Vi IgG potency for the US reference. Based on the correlation, we developed a statistical model to transform data from the in-house ELISA (μg/ml) to the Vacczyme ELISA (EU/ml) in the Vi-DT phase 1 study [19].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we confirmed previous results of collaborative study that a good concordance was observed between the Vacczyme ELISA and the IVI in-house ELISA, and both assays are commutable [18]. Amongst the various ELISA formats used in this study, the IVI in-house ELISA was demonstrated as a credible non-commercial alternative for the Vacczyme ELISA.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations